1989
DOI: 10.1002/jcla.1860030609
|View full text |Cite
|
Sign up to set email alerts
|

Ca 72‐4 radioimmunoassay for the detection of the tag‐72 carcinoma‐associated antigen in serum of patients

Abstract: Monoclonal antibody (MAb)B72.3 has been used to detect the presence of TAG-72 in the serum of carcinoma patients. We have developed new anti-TAG-72 MAbs and have selected one of these, CC49, as the "catcher" MAb with 125I-B72.3 as the detecting antibody in a double-determinant immunoradiometric assay. This combination enabled the development of a sequential assay (designated CA 72-4) that showed optimal quantitative properties as demonstrated by such parameters as linear dose-response, high re-producibility, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 14 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…2121 Double histochemical staining with antibodies to CEA and TAG-72 revealed that the two antibodies, in combination, reacted 26 In addition, Ohuchi et al confirmed that when monoclonal antibodies B72.3 and COL-6 (anti-CEA antibody) were simultaneously reacted with the gastric carcinoma tissue, more carcinomas were detected than with each individual antibody allone. 2 ' We found that CEA was expressed in 90% of the gastric tumors and TAG-72 was in 72.5% of lesions.…”
Section: Discussionmentioning
confidence: 85%
“…2121 Double histochemical staining with antibodies to CEA and TAG-72 revealed that the two antibodies, in combination, reacted 26 In addition, Ohuchi et al confirmed that when monoclonal antibodies B72.3 and COL-6 (anti-CEA antibody) were simultaneously reacted with the gastric carcinoma tissue, more carcinomas were detected than with each individual antibody allone. 2 ' We found that CEA was expressed in 90% of the gastric tumors and TAG-72 was in 72.5% of lesions.…”
Section: Discussionmentioning
confidence: 85%
“…At this time, TAG‐72 is widely recognized as a serum tumor marker, in the monitoring of gastrointestinal adenocarcinomas 8 . The limit values usually employed in the literature range between 4.0 and 10 U/mL, the most common being 6.0 U/mL 9 . The information provided in the ELSA CA 72–4 kit indicates that in a group of 200 healthy adult subjects, 98.5% showed values lower than 4 U/mL.…”
Section: Discussionmentioning
confidence: 99%
“…At present, immunoassay for the determination of CA72-4 is mainly radioimmunoassay (RIA) [2,[13][14][15] and enzyme-linked immunoadsorbent assay (ELISA) [16,17] . The disadvantages in using the RIA methods [2,[13][14][15] , however, are that it requires special disposal and demonstrates a stability problem and long detection period. On the other hand, ELISA methods [16,17] show low detection limit (0.31 U/mL), narrow linear range (0-100 U/mL), and long conduction time.…”
Section: Analytical Chemistrymentioning
confidence: 99%